Analiza elementov insiderskega posla - Samec Berghaus, Nataša (Podjetje in delo, 2014)
The prohibited insider dealing causes harm to the economy with reducing confidence in the regulated markets. It is difficult to recognize it, prove it, and, accordingly, to sanction it. Not even a single conviction for the criminal offense of misuse of inside information is available in publicly accessible databases of judicial decisions in Slovenia since its independence. Insider dealing is regulated with the two-tier regulation, as along as the sectorial legislation (Financial Instruments Market Act - ZTFI) and also Criminal Code (KZ-1) provides sanctions for insider dealing. The definition of criminal offense of misuse of inside information is narrower in the Criminal Code than in the ZTFI's provision prohibiting insider dealing. However, Article 238 of KZ-1 should be applied in conjunction with the provisions on insider dealing in ZTFI, although it is not a blanket norm. KZ-1 does not define three objective elements of the criminal offense of misuse of inside information - among them also the central element, i.e. "inside information" - and it in general inadequately defines insider dealing. The elements of inside information (accuracy, public nature, important influence on financial instruments pricing) and the issue of its use are the most complex questions in determining the violation of insider dealing. Thus, the author pays special attention to them in this article, as he analyses the facts that should be known: to the subject to whom the prohibition of insider dealing is directed to, to the offence authority (ATVP), to the law enforcement authority, collecting evidence and writing the charge, and to the judge when determining decisive facts.
Keywords: finančni instrumenti; notranje informacije; podjetja; zloraba